Konsumsi Kopi Mengurangi Angka Kematian pada Pasien dengan Infark Miokard Akut - Johan, Kenneth; Cahyanur, Rahmat; Resultanti, Resultanti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Aim: Acute myocardial infarction (AMI) is the number one cause of death in 2000. Usually, coffee restriction was advised to patients with cardiovascular diseases. Recent studies indicate coffee might have a cardioprotective effect.Method: Systematic search was done on Pubmed and Cochrane. Title and abstract screening were initiated on 12 articles, followed by selection with inclusion and exclusion criteria, and selected one meta-analysis study to be critically appraised. Result: The meta-analysis study appraised resulted with a good score. Reduction in mortality rate was found, and an inverse relationship was concluded between heavy coffee consumption versus no consumption and mortality in acute myocardial infarction patients. RR = 0.54 95% CI [0.45 – 0.65].Conclusion: Coffee consumption and mortality in myocardial infarction patients have an inverse relationship, with the highest risk reduction found in heavy coffee drinkers.